A Comprehensive Review on the Main Honey Authentication Issues: Production and Origin. Issue 5 (30th June 2017) - Soares, Sónia; Amaral, Joana S.; Oliveira, Maria Beatriz P.P.; Mafra, Isabel
Abstract: Honey is a highly consumed natural product, not only for its taste and nutritional value, but also for its health benefits. Owing to characteristics that are essentially or exclusively related to the specific region or particular local environment and flora, honey can be classified as a premium product generally perceived as a high‐quality and valued product because of its desirable flavor and taste. Consequently, honey has been a target of adulteration through inappropriate/fraudulent production practices and mislabeling origin. Globally, authentication of honey covers 2 main aspects: the production, with main issues related to sugar syrup addition, filtration, thermal treatment, and water content; and the labeled origin (geographical and/or botanical) and "organic" provenance. This review addresses all those issues, focusing on the approaches to detect the different types of honey adulteration. Due to the complex nature of honey and to the different types of adulteration, its authentication has been challenging and prompted the development of several advanced analytical approaches. Therefore, an updated, critical, and extensive overview on the current and advanced analytical methods targeting markers of adulteration/authenticity, including nontarget fingerprint approaches will be provided. The most recent advances on molecular, chromatographic, and spectroscopic methodologies will be described, emphasizing their pros and cons for the identification of botanical and geographical origins.